Décomposition photocatalytique du méthanol sur des nanosphères de TiO₂ chargées de métal - Vu, Thuy-Dung (Université Laval, 2019)
353121\u === 353121\u === The utilization of solar light-driven photocatalysts has attracted an increasing attention in creating green energy and purifying environment from harmful pollutants. In photocatalysis technology, semiconductor-based photocatalysis has diverse applications including the decomposition of organic pollutants. In particular, titanium dioxide (TiO₂)-based photocatalysts have been extensively studied because of their low cost and outstanding physical and chemical properties. However, the photocatalytic performance of TiO₂ is not very high due to the weak light absorption and the fast charge carrier recombination. Therefore, the main target of the research presented in this thesis is to develop new methods to prepare more efficient materials based on TiO₂ for organic pollutants decomposition. For this purpose, the uniform titanate nanodisks (TNDs) with an average diameter of 22 nm were first synthesized by using different types of capping agents, including benzyl alcohol (BA), benzyl ether (BE) and oleylamine (OM). SiO₂ nanospheres (SiO₂ NSs) in nanoscale diameter as the core of the structure were then coated with TNDs using a layer-by-layer deposition technique in the presence of polyethylenimine (PEI) solution to design the TND-PEI/SiO₂ NSs. Based on the developed TND-PEI/SiO₂ NSs, creating a heterojunction between TiO₂ and other visible light active semiconductors is one of the interesting ways to optimize and enhance performance of TiO₂ in the visible region. In order to synthesize these TiO₂-based heterojunction composites, several cation (Cu²⁺, Ni²⁺, and Pt²⁺) solutions were loaded over TND-PEI/SiO₂ NSs to obtain CuO/TiO₂/SiO₂, Ni²⁺/TiO₂/SiO₂ or Pt²⁺/TiO₂/SiO₂ materials, respectively. The co-existence of CuO, Ni²⁺, and Pt²⁺ functioning as co-catalysts led to a remarkable enhancement of the photocatalytic performance of TiO₂. The new developed materials have shown not only high porosity and high specific surface area, but also strong solar light absorption. As a result, the photocatalytic activity of these new materials and the effect of different co-catalysts were investigated in the photocatalytic decomposition of methanol. TiO₂-based heterojunction composites (CuO/TiO₂/SiO₂) was further treated by H₂S. This non-metal doping TiO₂ is a well-known and effective way to decrease the band gap, which can result in the absorption of more visible light. The photodegradation of methanol in aqueous solution was deployed to test the photocatalytic activities of TiO₂-based material and further widens its applications in water treatment. These modifications proved that the light absorption of CuO/TiO₂ was improved compared with Ni²⁺/TiO₂ and Pt²⁺/TiO₂. CuO/TiO₂ material after H₂S treatment was found to exhibit a good performance in the degradation of methanol from aqueous solutions under solar light irradiation. === The utilization of solar light-driven photocatalysts has attracted an increasing attention in creating green energy and purifying environment from harmful pollutants. In photocatalysis technology, semiconductor-based photocatalysis has diverse applications including the decomposition of organic pollutants. In particular, titanium dioxide (TiO₂)-based photocatalysts have been extensively studied because of their low cost and outstanding physical and chemical properties. However, the photocatalytic performance of TiO₂ is not very high due to the weak light absorption and the fast charge carrier recombination. Therefore, the main target of the research presented in this thesis is to develop new methods to prepare more efficient materials based on TiO₂ for organic pollutants decomposition. For this purpose, the uniform titanate nanodisks (TNDs) with an average diameter of 22 nm were first synthesized by using different types of capping agents, including benzyl alcohol (BA), benzyl ether (BE) and oleylamine (OM). SiO₂ nanospheres (SiO₂ NSs) in nanoscale diameter as the core of the structure were then coated with TNDs using a layer-by-layer deposition technique in the presence of polyethylenimine (PEI) solution to design the TND-PEI/SiO₂ NSs. Based on the developed TND-PEI/SiO₂ NSs, creating a heterojunction between TiO₂ and other visible light active semiconductors is one of the interesting ways to optimize and enhance performance of TiO₂ in the visible region. In order to synthesize these TiO₂-based heterojunction composites, several cation (Cu²⁺, Ni²⁺, and Pt²⁺) solutions were loaded over TND-PEI/SiO₂ NSs to obtain CuO/TiO₂/SiO₂, Ni²⁺/TiO₂/SiO₂ or Pt²⁺/TiO₂/SiO₂ materials, respectively. The co-existence of CuO, Ni²⁺, and Pt²⁺ functioning as co-catalysts led to a remarkable enhancement of the photocatalytic performance of TiO₂. The new developed materials have shown not only high porosity and high specific surface area, but also strong solar light absorption. As a result, the photocatalytic activity of these new materials and the effect of different co-catalysts were investigated in the photocatalytic decomposition of methanol. TiO₂-based heterojunction composites (CuO/TiO₂/SiO₂) was further treated by H₂S. This non-metal doping TiO₂ is a well-known and effective way to decrease the band gap, which can result in the absorption of more visible light. The photodegradation of methanol in aqueous solution was deployed to test the photocatalytic activities of TiO₂-based material and further widens its applications in water treatment. These modifications proved that the light absorption of CuO/TiO₂ was improved compared with Ni²⁺/TiO₂ and Pt²⁺/TiO₂. CuO/TiO₂ material after H₂S treatment was found to exhibit a good performance in the degradation of methanol from aqueous solutions under solar light irradiation.